2013
DOI: 10.1128/aac.02328-12
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect between Colistin and Bacteriocins in Controlling Gram-Negative Pathogens and Their Potential To Reduce Antibiotic Toxicity in Mammalian Epithelial Cells

Abstract: e Pathogens resistant to most conventional antibiotics are a harbinger of the need to discover novel antimicrobials and anti-infective agents and develop innovative strategies to combat them. The aim of this study was to assess the in vitro activity of colistin alone or in combination with two bacteriocins, nisin A and pediocin PA-1/AcH, against Salmonella choleraesuis ATCC 14028, Pseudomonas aeruginosa ATCC 27853, Yersinia enterocolitica ATCC 9610, and Escherichia coli ATCC 35150 (O157:H7). The strain most se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 33 publications
(31 reference statements)
3
54
0
Order By: Relevance
“…[23,24] Previous studies have shown that antibiotics, while intended to target bacteria, can have detrimental effects on viability and function of host cells in vitro. [25,26] This toxic effect seen in vitro could lead to breakdown of the soft tissue, fenestration, and dehiscence in vivo. It is also possible that the combination of gelatin and colistin may lead to increased local toxicity if the gelatin causes increased tissue exposure to colistin by retaining released colistin in the area.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] Previous studies have shown that antibiotics, while intended to target bacteria, can have detrimental effects on viability and function of host cells in vitro. [25,26] This toxic effect seen in vitro could lead to breakdown of the soft tissue, fenestration, and dehiscence in vivo. It is also possible that the combination of gelatin and colistin may lead to increased local toxicity if the gelatin causes increased tissue exposure to colistin by retaining released colistin in the area.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that AMPs, including SMAP29 and LL-37, can permeabilize the bacterial cytoplasmic membrane (26,27), as did P3, which created many membrane pores in the E. coli membrane, in line with the barrel stave model (28). It is generally considered that AMPs exhibiting potent antimicrobial activities also have strong hemolytic and cytotoxic activities (29). However, hemolysis did not exceed 20% after treatment of red blood cells with P3 or its analogs at 400 g/ml, a concentration approximately 60-fold higher than the MIC.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of LAB bacteriocins in medical applications is exemplified by previously reported results which indicated that the oral intake of bacteriocin-producing LAB protects mice from lethal doses of Listeria monocytogenes (7). Therefore, LAB bacteriocins are the logical alternative to clinical antibiotics (8) and/or may help to enhance the efficacy of current antibiotics (9,10).…”
mentioning
confidence: 88%